Everolimus‐Related Pneumonitis in Patients with Metastatic Breast Cancer: Incidence, Radiographic Patterns, and Relevance to Clinical Outcome. (7th December 2020) - Gong, Chengcheng; Xiao, Qin; Li, Yi; Gu, Yajia; Zhang, Jian; Wang, Leiping; Cao, Jun; Tao, Zhonghua; Zhao, Yannan; Xie, Yizhao; Hu, Xichun; Wang, Biyun
Abstract: Background: This study investigated the incidence, radiographic patterns, and relevance to clinical outcome of everolimus‐related pneumonitis (ERP) in patients with metastatic breast cancer (MBC). Materials and Methods: Data of patients with MBC treated with everolimus who had baseline and at least one follow‐up chest computed tomography (CT) were obtained from a medical electronic database system. An independent review of the CT scans of these patients was conducted by two radiologists (NCT 03730428). Log‐rank and Cox proportional hazard regression analyses were used for time‐to‐event analyses. Results: ERP was radiographically detected in 45 of 86 patients (52.3%). In more than 80% of these patients, ERP occurred during the first 4 months of everolimus treatment. Only 14 of the 45 patients with ERP were symptomatic (31.1%). Symptoms included cough, fever, and shortness of breath. Bilateral and lower distribution of the pneumonitis was most common. In most of the cases, ground‐glass opacities and reticular opacities were noticed. Elderly patients were more likely to develop ERP. Patients with ERP had significantly longer progression‐free survival (PFS; 6.8 vs. 4.1 months, p = .024) and overall survival (OS; 42.8 vs. 21.3 months, p = .016). ERP was a predictor of OS improvement confirmed by multivariate Cox analysis (hazard ratio, 0.49; 95% confidence interval, 0.25–0.97; p = .040). Conclusions: ERP was noted in half of the patients with MBC treated with everolimus. Our data suggested that ERP was associated with improved prognosis and may be used as a biomarker for the efficacy of everolimus in MBC. Close monitoring, prompt diagnosis, and proper treatment for ERP are essential to maintain the quality of life of patients and achieve maximum treatment benefits. Implications for Practice: Everolimus‐related pneumonitis (ERP) is one of the most worrying drug adverse events, especially in Asian patients. However, little has been known about the clinical and radiographic details of ERP in patients with metastatic breast cancers (MBCs) treated with everolimus. The present study investigated the clinical characteristics, radiographic patterns, and its correlation with treatment outcome in patients with MBC. ERP was identified in more than half of patients with MBC during everolimus therapy and was associated with improved outcome. Close monitoring and prompt diagnosis and appropriate treatment for ERP are critical for the preservation of patients' quality of life and achievement of maximal treatment benefits. Abstract : Evidence‐based guidelines for early diagnosis and effective treatment of everolimus‐related pneumonitis are urgently needed. This article reports on incidence, radiograph findings, and risk factors for everolimus‐related pneumonitis in patients with metastatic breast cancer.